The role of personality and anger in the explanation of youth women’s risky driving behaviours - Gómez Fraguela, José Antonio; González Iglesias, Beatriz (Anales de Psicología / Annals of Psychology, 2010)
The aim of this paper is to analyze the role of personality and anger in the explanation of youth women’s risky driving behaviour. One hundred and forty college students with driver's license completed meas-ures of personality (NEO PI-R), anger (STAXI-2 and DAS) and risky driving behaviour (DBQ). Results indicate that sensation seeking and driving anger predict involvement in aggressive driving and road traffic violations. On the other hand, errors and lapses committed by drivers are associated with personality variables, such as Agreeableness, Conscientiousness and Neuroticism. These results have important implications in the design of prevention and intervention programs in the field of road safety.